2018
DOI: 10.1136/bmjgh-2017-000687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a home-based participatory play intervention on infant and young child nutrition: a randomised evaluation among low-income households in El Alto, Bolivia

Abstract: BackgroundStunting affects child survival and is a key indicator of child well-being. Therefore, reducing stunting is a global goal. Improving infant and young child feeding (IYCF) practices is a recommended approach to reduce the risk of mortality and ameliorate nutritional status. Behavioural change interventions have the potential to improve IYCF practices.MethodsWe evaluated the effectiveness of an innovative behavioural change strategy on caregiver’s knowledge, IYCF practices and nutritional status of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The duration of visits for the RCF&P group was longer (25 min) that for the CF group (18 min). However, interactive play interventions have employed longer home visits (60-90 min) than the present study and have reported positive outcomes as a result of these longer visits (Martinez et al, 2018). In a low-or middle-income country context such as India, the cost of longer visits has to be considered within the programming strategy and weighed against the benefits that it achieves when resources are limited.…”
Section: Discussionmentioning
confidence: 70%
“…The duration of visits for the RCF&P group was longer (25 min) that for the CF group (18 min). However, interactive play interventions have employed longer home visits (60-90 min) than the present study and have reported positive outcomes as a result of these longer visits (Martinez et al, 2018). In a low-or middle-income country context such as India, the cost of longer visits has to be considered within the programming strategy and weighed against the benefits that it achieves when resources are limited.…”
Section: Discussionmentioning
confidence: 70%
“…The six eligible studies included four randomised controlled trials (Iannotti et al, 2014; Martinez et al, 2018; Smuts et al, 2019; Strand et al, 2015) and two cluster‐randomised controlled trials (More et al, 2017; Tomlinson, Rotheram‐Borus, Scheffler, & le Roux, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies involved home-based visits: one included promotion of optimal IYCF practices by trained 'Mentor Mother' community health workers (Tomlinson et al, 2018) and one incorporated play-based nutritional education messages (Martinez et al, 2018). Only one study took an integrated community-based approach with the introduction of local resource centres in addition to home visits and day-care centre interventions (More et al, 2017).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…We analysed panel data from a community nutrition programme in Bolivia that collected rich child nutrition, food consumption and household demographic and socio‐economic survey data (Martinez et al, 2018). The survey was implemented in the eighth district of El Alto, a low‐income, predominately indigenous population where all households have access to electricity, but there is substantial variation in refrigerator ownership.…”
Section: Methodsmentioning
confidence: 99%
“…Child nutrition was assessed using the following anthropometrics measures: (1) height‐for‐age z score, (2) weight‐for‐age z score, (3) weight‐for‐height z score and (4) BMI‐for‐age z score. Height and weight were measured using standardized methods (Martinez et al, 2018). Height was measured using a wood infantometer, and weight was measured using a SECA scale with a precision of ±50 g; z scores were calculated from raw height and weight measures using the WHO Anthro Software in Stata.…”
Section: Methodsmentioning
confidence: 99%